Stable isotope ecology of Quaternary cervid and bovid species in Southeast Asia with implications for wildlife conservation - Sanah Shaikh; Hervé Bocherens; Kantapon Suraprasit (Scientific Reports)
Abstract Southeast Asia, one of the major biodiversity hotspots, is experiencing substantial species loss, with predictions indicating that 13–85% of species are threatened to lose their original habitats. As herbivores play a crucial role in shaping the structure of environments and the ecosystem dynamics of the region, it is crucial to protect these endangered species. Here we measure stable carbon isotopic ratios (δ 13C) of tooth enamel samples of eight extant Southeast Asian cervid and bovid taxa, mostly listed as either endangered or vulnerable species by the IUCN and compare the results with their Pleistocene counterparts, in order to investigate their dietary and preferred habitat changes through time. As a result, three distinct categories of ecological patterns among these ruminant taxa are observed: (1) species with dietary and habitat changes through time (i.e. Axis axis, Rucervus eldii, Bos javanicus, and Bos gaurus), (2) those with more restricted diets and habitats today than in the past (i.e. Rusa unicolor and Bubalus arnee), and (3) those with unchanged diets and habitats over time (i.e. Axis porcinus and Muntiacus muntjak). In the case of species with dietary and habitat changes, the Pleistocene C4-grazer enamel isotopes showed a shift towards greater reliance on C3 plants or more closed environments during the Holocene. The isotopic evidence raises the question of whether climatic and environmental changes and/or anthropogenic pressure have significantly driven the population decline of threatened species and can contribute to the understanding of future conservation outlooks of existing wildlife populations in Southeast Asia.